Scientific Aspects of Water Extract Katola (Arcangelisia flava L. Merr) as Antidiarrhea Agent in Mina South Sulawesi - Muhammad Akhram Larisu; Sudarsono .; Susi Iravati; Arief Nurrochmad (Indonesian Journal of Pharmacy, 2010)
Water  extract  of  katola  (Arcangelisia  flava  L.  Merr)  stem  is  traditionally used in communities Muna Distric for the treatment of many diseases, including anti  diarrhea.  According  to  the  information  of  Muna  Distric  Health  Office, diarrhea  is  one  of  the  10  groups  diseases  in  this  district.  The  objective  of  this study was conducted to determine the potential antimicrobial, acute toxicity and identified  of  the  water  extract  of  bioactive  compounds  and  alkaloid  relative concentration content.  Infection of microbial was induced by oral administration of  Shigella  flexneri  ATCC  12022  1  x  108 CFU/mL.  Boiling  water  of  katola  dose 12  mg/kg,  24  mg/kg  and  48  mg/kg  body  weight  and  the  antibiotic  ampicillin 24  mg/kg  administered  2  times  daily  for  5  days.  The  number  of  S.  flexneri  in feces were determined every day. The toxicity of water extract of  katola stem  is determined  based  on  the  value  of  LD50  acute  oral  toxicity  testing  followed  by guidelines  OECD  423. The  bioactive compounds was determined by bioautografi method  and  the  concentration  alkaloid  relative  content  was  calculated  as berberine  hydrochloride.  The  results  showed  that boling  water extract of  katola stem  did  not  cause  toxic  symtoms,  with  LD50  >  31.5  g/kg  body  weight (unclassified)  or  104  times  the  dose  therapy  of  human.  In  vitro,  the  Minimum Inhibition  Concentration  (MIC)  and  Minimum  Bactericidal  Concentration (MBC)value  of  the  boiling  water  were  1.2  and  2.4%,  respectively.  In  vivo,  the boiling  water  dose  48  mg/kg  body  weight  given  twice  a  day  have  an  effect  on eradication the S. flexneri 100% by day 5. Bioactive compounds of antimicrobial in  the  water  extract  is  alkaloid  berberine  HCl.    A  cocentration  of  berberine hydrochloride  in  water  exract  stem  and  leaves  dosage  use  of  the  public  were 16.7% and 0.75% respectively.Key words: Katola, toxicity, anti diarrhea, antimicroba, Arcangelisia flava L. Merr